A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India - Shangningam, Bungdon; Kosygin, Laishram; Sinha, Bikramjit (Zootaxa, 2019)
A new species of the genus Garra is described from the Ranga River of the Brahmaputra basin, Arunachal Pradesh, northeastern India. Garra magnacavus, new species, differs from its congeners in having an incipient proboscis with a transverse lobe, 15−19 rounded large pits on the snout, weakly developed non-fleshy central callous pad, and an elongate body with 42 lateral-line and 14−16 predorsal scales.